Preparation of chitosan/sodium alginate conductive hydrogels with high salt contents and their application in flexible supercapacitors. (15th February 2022) - Peng, Kelin; Wang, Weizhe; Zhang, Jinghua; Ma, Yan; Lin, Lizhi; Gan, Qiang; Chen, Yu; Feng, Changgen
Abstract: Conductive hydrogels (CHs) are a potential material for flexible electronics. However, most of CHs display disadvantages of low ionic conductivities and intolerance to low temperatures. Herein, a novel physical CHs with salt contents as high as 30 wt% was prepared with chitosan (CTS) and sodium alginate (SA) by combining the anti-polyelectrolyte effect and semi-dissolution acidification sol-gel transition (SD-A-SGT) method. The obtained hydrogels show extremely high ionic conductivities up to 2.96 × 10 −1 S·cm −1 at room temperature and 4.9 × 10 −2 S·cm −1 at −20 °C. The effects of different salts on the ion mobility and electrochemical properties of CTS/SA CHs were predicted and analyzed. The flexible supercapacitor assembled using CTS/SA CHs as the electrolyte exhibits the specific capacitance as high as 405 F·g −1 at the current density of 0.25 A·g −1 and satisfying electrochemical stability with 74.91% capacitance retention in 1000 cycles. Our work has provided a new strategy for constructing green CHs with high ionic conductivities. Graphical abstract: Unlabelled Image